Meningitis outbreak caused by vaccine-preventable bacterial pathogens — Northern Ghana, 2016 - Aku, F.Y.; Lessa, F.C.; Asiedu-Bekoe, F.; Balagumyetime, P.; Ofosu, W.; Farrar, J.; Ouattara, M.; Vuong, J.T.; Issah, K.; Opare, J.; Ohene, S.-A.; Okot, C.; et al. (Morbidity and Mortality Weekly Report, 2017)
What is already known about this topic? The introduction of serogroup A meningococcal conjugate vaccine (MenAfriVac) in Ghana in 2012 had a substantial impact on the periodic outbreaks of meningitis in the Northern Ghana. However, seasonal increases in bacterial meningitis continue to occur; the most prevalent etiologies are Neisseria meningitidis, Streptococcus pneumoniae, and Haemophilus influenzae. What is added by this report? During December 9, 2015-February 16, 2016, a total of 432 suspected meningitis cases were reported from three regions in northern Ghana. Among 286 cerebrospinal fluid specimens tested, 133 (46.5%) were positive, including 83 (62.4%) for N. meningitidis and 44 (33.1%) for S. pneumoniae. The predominant N. meningitidis serogroup was serogroup W (99%). Based on laboratory and epidemiologic data, 135,679 doses of meningococcal polysaccharide ACW vaccine were administered to the age groups most affected, resulting in substantial reduction in the number of meningitis cases. What are the implications for public health practice? Rapid identification of the etiologic agent in meningitis outbreaks is important for informing targeted public health interventions. Building and sustaining laboratory capacity in countries where meningitis outbreaks are common will be critical in ensuring rapid and effective response to these outbreaks. © 2017, Department of Health and Human Services. All rights reserved.
Keywords: Meningococcus vaccine; adolescent; adult; cerebrospinal fluid; child; Disease Outbreaks; female; Ghana; human; isolation and purification; male; Meningitis, Bacterial